A Markov-Switching Approach to Measuring Exchange Market Pressure - Kumah, Francis (IMF Working Papers; Working Paper ;, 2007)
This paper characterizes exchange market pressure as a nonlinear Markov-switching phenomenon, and examines its dynamics in response to money growth and inflation over three regimes. The empirical results identify episodes of exchange market pressure in the Kyrgyz Republic and confirm the statistical superiority of the nonlinear regime-switching model over a linear VAR version in understanding exchange market pressure. The nonlinear empirical approach adequately characterizes the data generation process and yields results that are consistent with theoretical predictions, particularly the dampening effect of monetary contraction on depreciation pressure. During periods of appreciation pressure, however, the reverse policy option-monetary expansion-may not be efficient, particularly where PPP rather than UIP drives exchange rates. In addition, monetary expansion in such cases defeats the primary objective of monetary policy-price stability-and may exacerbate the instability.